Exploring parental motivation in youth sports participation: A study of basketball club enrollment - Rindy Puspita Aryashanty; Soni Sulistyarto; Anna Noordia; Hijrin Fithroni (Universitas Sriwijaya, 2026)
Research Problems: Parental motivation plays an important role in encouraging children to participate in sports, including in choosing the type of sport and club. This motivation is influenced by various needs such as physiological needs, safety and comfort, social needs, esteem, and self-actualisation. Research Objectives: This study aims to identify parental motivation in enrolling their children in basketball clubs. Methods: This study used a quantitative descriptive approach. The sample consisted of 30 parents selected purposively from a population of 200. Data were collected using a questionnaire based on the hierarchy of needs. Results: The dominant motivation was safety and comfort needs (28%), followed by social needs (25.8%), physiological needs (16.8%), esteem needs (14.7%), and self-actualisation (14.7%). Conclusion: Safety and comfort are the main considerations for parents. Therefore, sports clubs should create a safe and comfortable environment to increase children's participation.